[Symbol] Market - Webster, Tim (Timothy James), 1965- ([Melbourne?] : T. Webster, 2009)
A photographic biography of the Queen Victoria Market, Melbourne with text drawn from approx. 200 oral histories recorded and transcribed during the first few years of the century.
The symbol is an arrow pointing to the right.
Limited ed. of 100 handmade books signed by the photographer.
The photographer and feature writer is based in Melbourne. His work focusses on cultural and environmental themes.
Keywords: Queen Victoria Market (Melbourne, Vic.) -- Pictorial works; Markets -- Victoria -- Melbourne -- Pictorial works